Is Olympic Communication-Activity a Means for the Construction of Cosmopolitan Identities? - Patsantaras, Niko; Irene Kamberidou (Sports, Bodies, Identities and Organizattions: Conceptions and Problems, 2011)
WHEN CITING: Patsantaras, N., & Kamberidou, I. (2011). Is Olympic Communication-Activity a Means for the Construction of Cosmopolitan Identities? In Sports, Bodies, Identities and Organizations: Conceptions and Problems (pp. 132–141). Wojciech J. Cunarski, Kazimierz Obodynski, Nicola Porro (Eds.). Publisher: Faculty of Physical Education, University of Rzeszow, under auspices of the European Association for Sociology of Sport (EASS). ISBN 978-83-7338-657-0. Copyright by Wydawnictwo Uniwersytetu Rzesowskiego Rzeszow 2011. ------------------------------------------------------------------------------------------------------------- Cultural Identity and Olympic Sports. In the last decades accelerated and unrestrained structural and institutional changes—on an institutional level— have been shattering significant cultural spheres such as class, gender, nationality, nation, and so forth. Today, due to social transformations individual/personal identities are changing and undermining, our sense of self as complete subjects. Namely, the social subject is losing his/her autonomy and self-sufficiency. Identity is no longer formulated on the basis of the social subject’s inner nucleus but is constructed in the interrelations of the self with the social values, meanings and symbols (culture) of the world in which we live and act in [Hall, Held, McGrew 1992]. Social identity is no longer focused on the self as the centre but on the social-cultural environment and as a result identities are being transformed due to structural and institutional changes.  The postmodern social subject, in this framework and as a rule, cannot have a stable, static or permanent identity. The social subject— athlete, individual as well as diverse social groups— is confronted with different representations according to socio-cultural conditions.  Olympic sports, as a relatively autonomous socio-cultural system, exercise a dynamic influence on the social subject— who acts and communicates within its structures— in the construction of personal/individual identities as well as collective identities. For example, since 1981 the changes that came about with the official recognition of the commercialization of Olympic activity, for some meant deviance and for others adaptation to transforming-evolving social processes.  Significant here are the changes regarding Olympic social reality— the material and structural conditions that influence the formation of identity— which affect the active participants as well as the passive ones. In our postmodern period, identities are continuously formed, transformed and reconstructed in relation to the ways that we are represented or addressed in the cultural system that surrounds us (Donnelly, Young 1988).   Keywords: globalization, cosmopolitanism, ecumenical values, collective identity, diverse identities, sport identity.